Alloexidiopsis gen. nov., A Revision of Generic Delimitation in Auriculariales (Basidiomycota) - Liu, Shi-Liang; Shen, Zi-Qi; Li, Qian-Zhu; Liu, Xiang-Yang; Zhou, Li-Wei (Frontiers in Microbiology, 2022)
Auriculariales is a fungal order with highly diverse morphological traits of basidiomes, which partially leads to a poor understanding on its taxonomic system at the generic level. To identify our recently collected specimens of Auriculariales to a species level, we perform a comprehensive phylogenetic analysis on the generic relationships in Auriculariales. In association with morphological characters, a new genus Alloexidiopsis belonging to Auriculariaceae is erected with two new species A. australiensis and A. schistacea. Moreover, Exidiopsis calcea separated from the generic type E. effusa, and Heteroradulum niveum and H. yunnanense recently inappropriately described as members of Heteroradulum are recovered in the clade of Alloexidiopsis. These three species are thus transferred to this new genus. One collection of Exidiopsis grisea also falls in the clade of Alloexidiopsis, whereas another collection of this species is separated far from Alloexidiopsis as well as E. effusa. Since we have no collection to confirm the species identity of E. grisea, its generic position is uncertain. Main taxonomic morphological differences among Alloexidiopsis and related corticioid genera in Auriculariales are summarized. A key to all five accepted species of Alloexidiopsis is provided. As two unnamed lineages exist in Alloexidiopsis besides the above-mentioned five species, it is assumed that more new species will be revealed from this genus under its current circumscription.